Effect of the 12-gene colon cancer assay results on adjuvant treatment recommendations in patients with stage II colon cancer. (February 2014) - Cartwright, T.; Chao, C.; Lee, M.; Lopatin, M.; Bentley, T.; Broder, M.; Chang, E.
Abstract Introduction: The 12-gene colon cancer Recurrence Score assay is a clinically validated predictor of recurrence risk in stage II colon cancer patients. A survey was performed characterizing the assay's impact on treatment recommendations for these patients. Methods: US medical oncologists (n = 346) who ordered the assay for ≥3 stage II colon cancer patients were asked to complete a web-based survey regarding their most recent such patient. Physicians surveyed represented users of the assay within the first 2 years of commercial availability which may include 'early adopters'. Results: Most of 116 eligible physicians were in community practice (86%), with median 14.5 years' experience (range = 2–40). Mean patient age was 61 years (range = 32–85); 81% had T3 disease, and 38% had comorbidities. Of 76 patients tested for mismatch-repair/microsatellite-instability (MMR/MSI), 13 (17%) were MMR-deficient/MSI-high; 46 (61%) MMR-proficient/MSI-low; and 17 (22%) unknown. Most patients (84%) had ≥12 nodes examined. Median Recurrence Score result was 20 (range = 1–77). Before assay, treatment recommendations were specified for 92 (79%) patients, with no recommendation for 24 (21%). Of the 92 with pre-assay recommendations, chemotherapy was planned for 52 (57%) and observation for 40 (43%); the assay changed recommendations for 27 (29%). Treatment intensity decreased for 18 (67%) and increased for nine (33%) patients; it was more likely to decrease for lower Recurrence Score values and increase for higher values (p < 0.001). Conclusion: For stage II colon cancer patients receiving Recurrence Score testing, 29% of treatment recommendations were changed. Use of the assay may lead to reductions in treatment intensity. Study limitations include retrospective design, data gathering during the first 2 years of assay availability only, and potential non-representativeness of respondents.